Theoretical consideration on harmonic manipulated amplifiers based on experimental data - Raffo, Antonio; Colantonio, Paolo; Cipriani, Elisa; Vadala, Valeria; Bosi, Gianni; Martín-Guerrero, Teresa María; Vannini, Giorgio; Giannini, Franco (My University, 2015)
This contribution aims at the experimental confirmation of the advantages of the harmonic manipulation theory, using a low-frequency low-cost characterization setup. A 0.5-μm 10x100-μm (1-mm gate periphery) GaN HEMT has been characterized synthesizing at the current-generator plane different load conditions, realizing tuned-load and Class-F operation. The measurements clearly demonstrate the importance of by synthesizing the required loads at the correct reference plane, giving an experimental proof of the performance predicted by theoretical analysis.
Keywords: Telecomunicaciones - Congresos; FET; Harmonic manipulation; Integrated circuit measurement; Microwave power amplifier; Semiconductor device measurement